Effects of exercise on circadian rhythms in humans - Shen, Bingyi; Ma, Changxiao; Wu, Guanlin; Liu, Haibin; Chen, Lihong; Yang, Guangrui (Frontiers in Pharmacology, 2023)
The biological clock system is an intrinsic timekeeping device that integrates internal physiology and external cues. Maintaining a healthy biological clock system is crucial for life. Disruptions to the body's internal clock can lead to disturbances in the sleep-wake cycle and abnormalities in hormone regulation, blood pressure, heart rate, and other vital processes. Long-term disturbances have been linked to the development of various common major diseases, including cardiovascular diseases, metabolic disorders, tumors, neuropsychiatric conditions, and so on. External factors, such as the diurnal rhythm of light, have a significant impact on the body's internal clock.Additionally, as an important non-photic zeitgeber, exercise can regulate the body's internal rhythms to a certain extent, making it possible to become a non-drug intervention for preventing and treating circadian rhythm disorders. This comprehensive review encompasses behavioral, physiological, and molecular perspectives to provide a deeper understanding of how exercise influences circadian rhythms and its association with related diseases.